2020
DOI: 10.2196/16524
|View full text |Cite
|
Sign up to set email alerts
|

Brief, Web-Based Interventions to Motivate Smokers With Schizophrenia: Randomized Trial

Abstract: Background In-person motivational interventions increase engagement with evidence-based cessation treatments among smokers with schizophrenia, but access to such interventions can be limited because of workforce shortages and competing demands in mental health clinics. The use of digital technology to deliver interventions can increase access, but cognitive impairments in schizophrenia may impede the use of standard digital interventions. We developed an interactive, multimedia, digital motivationa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 65 publications
0
34
0
8
Order By: Relevance
“…To accomplish this, more community mental health centers will need to begin offering smoking cessation services since many of these providers still do not include cessation treatment in their array of services. 43 While lower ICVH scores among females were also driven by a higher prevalence of poor dietary status compared to males, overall only 2.23% of all participants met criteria for ideal dietary status. This is lower than the 10.4% found in another study of ICVH in people with SMI, 26 but consistent with findings from a systematic review showing eight of 15 U.S. general population studies reported ideal diet prevalence of 1% or less and the remaining studies reported prevalence of 10% or less.…”
Section: Discussionmentioning
confidence: 90%
“…To accomplish this, more community mental health centers will need to begin offering smoking cessation services since many of these providers still do not include cessation treatment in their array of services. 43 While lower ICVH scores among females were also driven by a higher prevalence of poor dietary status compared to males, overall only 2.23% of all participants met criteria for ideal dietary status. This is lower than the 10.4% found in another study of ICVH in people with SMI, 26 but consistent with findings from a systematic review showing eight of 15 U.S. general population studies reported ideal diet prevalence of 1% or less and the remaining studies reported prevalence of 10% or less.…”
Section: Discussionmentioning
confidence: 90%
“…Nearly 80% of participants reported a 24-hour quit attempt during their participation in MCR-Q ( Table 5 )—a figure higher tha annual rates of serious quit attempts reported by individuals with psychotic-spectrum disorders in epidemiological studies (27-48%: [ 45 47 ]). It also exceeds the rate of serious quit attempts following participation in a web-based, motivational enhancing smoking cessation intervention for individuals with psychotics-spectrum disorders (30%: [ 48 ])—the only previous study to report rates of quit attempts among individuals with psychotic-spectrum disorders participating in a psychosocial smoking cessation intervention.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were individually randomized (but not cluster‐randomized) controlled trials, conducted within a single country, in an outpatient or community setting. Seven studies were conducted in the United States [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ], two in the United Kingdom [ 14 , 32 ] and two in Australia [ 33 , 34 ]. One study did not clearly state the country [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six of the studies recruited participants with schizophrenia or schizoaffective disorder [ 25 , 27 , 28 , 29 , 33 , 36 ], five included participants with schizophrenia, schizoaffective disorder or bipolar disorder [ 14 , 31 , 32 , 34 , 35 ] and one recruited participants with bipolar disorder only [ 30 ]. Seven studies had a requirement that participants had stable symptoms and/or dose of medication [ 28 , 29 , 30 , 31 , 33 , 34 , 35 ] and five studies did not state whether participants had stable symptoms and/or medication [ 14 , 25 , 27 , 32 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation